Cover Image: Barley and wheat biology. Issue 3 (18th March 2019) - Unknown
Abstract : Wheat and barley were among the first crops in the Fertile Crescent. From there they started to successfully conquer our plates. Haas et al. (204–225) give an update to what we know about the domestication genomics of these two major cereals. Their highly complex genomes only recently became accessible for more detailed analyses through advanced sequencing techniques.